Factors Increasing red Blood Cell Aggregation in Men with Coronary Artery Disease - Boss, N.; Bruder, W.; Bierner, M.; Koenig - Erich, S.; Fleck, E.; Ruhenstroth-Bauer, G. (Thrombosis and Haemostasis, 1979)
Red blood cell aggregation value (AW) was found to be of good diagnostic value ror coronary artery disease. Causes of increased aggregation value were investigated by means of protein analytical methods and standard laboratory techniques in 41 men with angiographically documented coronary artery disease. Best correlation coefficients were found between the red blood cell aggregation value and IgG, precipitable by 25g/1 polyethyleneglycol 6000 (r = 0.536; 2P ≤ 0.001). In coronary artery disease patients with no previous myocardial infarction (N=15) polyethyleneglycol precipitable IgM was found to correlate best with red blood cell aggregation (r = 0.707; 2P ≤ ! 0.01 ). In contrast to these results, patients without coronary stenosis demonstrated no significant correlation between the red blood cell aggregation value and the latter factorsThese results indicate a possible link between coronary artery disease, immune complexes and red blood cell aggregation. Platelet aggregation, as well as the coagulation system may also be influenced by these possibly specific immune complexes.